46.6k views
2 votes
The equation ey = 2x is equivalent to y = ln 2y = In x y = ln 2x.




User Ryan Grush
by
5.7k points

2 Answers

4 votes

Answer:

Y=ln 2x

Step-by-step explanation:I just did it on edg 2020

User Charith Jayasanka
by
5.5k points
4 votes

Answer:


y=ln(2x)

Explanation:

we have


e^(y)=2x

Applying ln both sides


ln(e^(y))=ln(2x)


y*ln(e)=ln(2x)

Remember that


ln(e)=1

substitute


y=ln(2x)

User Lzap
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.